Development of a neutron probe for Carbon-to-Oxygen (C/O) oil logging equipped with a high-temperature alpha particle detector. (1st May 2022) - Sudac, D.; Valkovic, V.; Nad, K.; Orlic, Z.; Uroic, M.; Batur, J.; Vinkovic, A.; Eres, Z.; Gacina, M.; Perkovic, A.; Korolija, M.; Rendic, D.; et al.
Highlights: A neutron probe for oil logging was developed with an outside diameter of 43 mm. NP was equipped with a four-segmented alpha particle detector operable at high temperatures. The possibility of measuring the C/O ratio as a function of the angle around the NP axis was shown. Measurements were done on geological samples taken from Croatian oilfields. Measurements on the high-temperatures show degradation of the signal coming from the gamma-ray detector. Abstract: A recently developed concept of a neutron probe (NP) -for C/O oil logging, based on associated alpha particle technique, has been developed and demonstrated by using a specially constructed NP. The NP contains a high-temperature alpha particle detector as well as a gamma detector with high energy resolution, suitable for a high-temperature environment. The probe was tested on samples collected from Croatian oil fields and on samples prepared with known C/O ratios. This NP in comparison to conventional neutron activation probes significantly reduces the background signal coming from the borehole and measures the C/O ratio depending on the azimuth angle around the borehole longitudinal axis. The time (position) resolution was found to be 2 ns enabling inspection of the C/O ratio in rock formations' layers down to 10 cm thickness. The NP was successfully tested for different environmental temperatures up to 175 °C. The pulse amplitude degradation coming from the gamma detector was noticed to be a function of the temperature.